Adaptive Human Resource Management Model for the Needs of Working Students at Universitas Terbuka - Salsabila, Selomita Dewi; Septia, Septia; Santoso, Yonatan Ari (Jurnal Ilmu Administrasi Negara (JUAN), 2025)
This study explores the development of an adaptive human resource management (HRM) model designed to address the specific needs of working students at Universitas Terbuka, Indonesia’s foremost open and distance learning institution. The background of this research arises from the increasing number of students who must balance professional responsibilities with academic commitments, leading to challenges related to time constraints, high stress levels, and the demand for flexible academic services. The main objective of this study is to analyze the current HRM practices at Universitas Terbuka, identify barriers that hinder adaptiveness, and formulate strategies to create a more inclusive and responsive management model. A qualitative case study approach was used, involving semi-structured interviews with students, lecturers, tutors, and administrative staff, complemented by document analysis and field observations. The collected data were thematically analyzed to uncover major patterns of adaptive and non-adaptive HRM practices within the institution. The findings reveal that effective adaptive HRM must emphasize three essential dimensions: strengthening educators’ pedagogical and empathetic competencies, restructuring administrative services through responsive digital systems, and revising institutional policies to promote flexibility and inclusivity. Despite significant progress in digital transformation, bureaucratic rigidity continues to limit the realization of truly flexible open education, creating implicit barriers for working students. The study concludes that achieving adaptive HRM requires empathy, participatory policy formulation, and cultural transformation as key foundations. Theoretically, this research enriches HRM discourse in higher education, while practically, it provides recommendations for continuous professional development, flexible administrative structures, and policy reforms that prioritize the realities of working students.